A POSSIBILITY OF REMOTE QUALITY CONTROL OF MATERIALS: BUILDING BRICKS AS AN EXAMPLE - Ovsyanikov, V.; Beznosova, O. (Radio physics and radio astronomy (Print), 2022)
Subject and Purpose. The subject of this research relates to quality parameters of substances with dielectric properties, while the main aim is development of a microwave-band remote sensing technique for measuring quality parameters of solids and loose materials. Methods and Methodology. The work is based on electromagnetic methods for determining substance quality by means of calculations and measurements of microwave signal attenuation in the substance of interest. The methods employed involve electrodynamic analysis of multilayered structures, the analytical method of moments, integral equations of diffraction theory, and objective function optimization. For a certain set of substances, preliminary calibrations and parameter storage are performed, intended for use in the determination of electromagnetic wave attenuation in the substance of interest. By comparing electromagnetic wave attenuation in the substance under testing with correspondent values shown by pre-calibrated samples, with their sets of parameters, it is possible to judge on the quality of the material under consideration. Results. By applying diffraction-theoretic methods of wave analysis in multilayered structures, the electromagnetic field attenuation in a substance (building bricks) has been calculated. The calculatеd results concerning electromagnetic signal attenuation in the test substance were compared with corresponding microwave measurements, thus permitting construction of the structural and mathematical model for the determination of the substance (building bricks) quality. The studies made it possible to evaluate the overall electrodynamic range of the measuring device, choosing the best options for the transmit and receive antenna sensors and the measuring equipment. The method of moments has been used to derive three-dimensional radiation patterns in the proximity of the device and the gain factor of the antenna sensors, wherefrom estimating the mutual electromagnetic effect that the sensors and the test substance may have on each other. Conclusion. Further development of the proposed method may imply refinement of the structural and mathematical models underlying estimation of quality parameters, determination of the overall dynamic range of the microwave-band measuring device, and provisions for automated real-time quality control and monitoring (for instance, on a conveyor), while maintaining conformance to applicable eco-standards concerning microwave intensity levels produced by the device.